VISUALISASI METODE PELAKSANAAN PEKERJAAN PELAT RAMP PROYEK PEMBANGUNAN GEDUNG WAREHOUSE DEPOK - Tati Noviati (Asosiasi Dosen Muda Indonesia, 2024)
The Project of Depok Warehouse Building Construction is located at JL. Raya Jakarta-Bogor, KM. 35, Jatijajar, Depok City, West Java, 16415. The project of Depok Warehouse Building is built on a land area of 38,000 m2, with a building area of 24,000 m2. The Depok Warehouse Building has 8 floors, consisting of 5 floors for the building area and 3 mezzanine floors used for offices. PT. Depok Logistik Properti is the owner of the project, PT. Trimatra Jasa Prakarsa as the construction management, PT. Gistama Intisemesta as the planning consultant, and PT. Total Persada Indonesia as the main contractor. The type of contract used is a lump sum with a contract value of Rp 350,000,000,000. The planned duration of the Warehouse Building Construction project is 670 days. Research made on the field include upper structure works such as column, beam, floor slab, and ramp slab. The stages of the implementation method for the ramp Truck Plate Work start from preparation, marking, reinforcement fabrication, reinforcement installation, concrete decking installation, reinforcement checklist, formwork installation, verticality test, casting, formwork removal, and concrete curing.